ARI updates 2009: Accounting Research Institute and Faculty of Accountancy - UiTM, Accounting Research Institute (Accounting Research Institute (ARI), 2009)
It is my great pleasure to extend heartiest congratulations to the Accounting Research Institute (ARI) for adding on yet another feather to its cap through the publication of ARI Updates 2009; and, it is with greater pleasure that I commend ARI for its remarkable achievement of having been granted the status of Higher Institution Centre of Excellence (HICoE) – one out of six – from the Ministry of Higher Education (MOHE). Indeed, such prestigious recognition augurs well not only for ARI but also UiTM, as it places the University alongside others whose research entities are ranked among the best at home.